Randomized Controlled Trial of Use of the Peanut Ball During Labor. Issue 3 (May 2016) - Roth, Cheryl; Dent, Sarah A.; Parfitt, Sheryl E.; Hering, Sandra L.; Bay, R. Curtis
Abstract: Purpose: The purpose of this study was to evaluate the efficacy of peanut ball use on duration of first stage labor and pushing time in women who were scheduled for elective induction of labor at ≥39 weeks gestation and planning an epidural. Study Design and Methods: In this randomized controlled trial, women having labor induction and planning a labor epidural were assigned (1:1) to one of two groups: one group used a peanut ball and one group did not. Outcome variables were time spent in first stage labor and time spent pushing. Factors included group assignment (peanut ball, no peanut ball), parity (primiparous, multiparous), and race. Age and maximum oxytocin dose served as covariates. Results: Among women having elective induction with epidural analgesia, use of a peanut ball reduced first stage labor duration for primiparous patients significantly more than multiparous patients, p = 0.018. There was no significant difference in the reduction of length of first stage labor for multiparous women, p = 0.057 with use of the peanut ball. Peanut ball use did not alter length of pushing time for either group, p > 0.05. Clinical Implications: Use of peanut balls may reduce total labor time to a greater degree in primiparous patients than multiparous patients having elective induction at ≥39 weeks with epidural analgesia. Abstract : The peanut ball is a specific type of birthing ball used by some women in labor. It may be helpful in maternal positioning and promoting labor progress. A randomized trial of peanut ball use is reported.